The Relationship between Learning Motivation and Learning Achievement in Students Organizing in the Faculty of Health Sciences, Muhammadiyah University of Surabaya - Hidayati, Siti Rohmatul; Reliani, Reliani; Nasrullah, Dede; Retnaningtyas, Ekowati (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2016)
Background: The results of interviews of 15 students who have low motivation are because students who are too active in organizations will generally be distracted by organizational activities such as meetings and activities outside of lectures, especially for students who have not been able to manage the time between lectures and the organization so that the consequence is that students One of the reasons for low motivation and learning achievement is that the academic score is not enough, even if it is not passed on time Learning achievement can be influenced by motivation, among others, starting from the stimulus process (stimulation) given to students can be accepted or rejected. If the stimulus is not accepted, it means that the stimulus cannot influence learning achievement. However, if students receive the stimulus well, then there is attention from the student, and the stimulus effectively affects learning achievement. If the stimulus is accepted, students understand this stimulus and proceed to the next process. After that, students process the stimulus so that there is a willingness to learn for the stimulus's sake. Finally, with the support of facilities and encouragement from the environment, the stimulus affects action or changes in student motivation to be more active in learning.Objective: To explore the relationship between learning motivation and learning achievement in students who organize at the Faculty of Health Sciences, University of Muhammadiyah Surabaya (UMSurabaya) the academic year 2014-2015.Methods: Cross-sectional approach to correlational analytic research.Results: The research results of 65 students organized at FIK UMSurabaya academic year 2014-2015 found the right learning motivation, namely as many as 33 (51%). The research results of 65 students organized at FIK UMSurabaya academic year 2014-2015 found outstanding learning achievement, namely 37 (58%).Conclusion: There is a relationship between learning motivation and student learning achievement in organizations at FIK UMSurabaya academic year 2014-2015.